Strategi Kepala Sekolah Meningkatkan Citra SMP melalui Daya Tarik Penerimaan Siswa Baru dan Penanganan Bullying - Wefri Wanaputra Sulistyan; Bukman Lian; Muhammad Juliansyah Putra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to identify and analyze the principal's strategies in enhancing school image through the analysis of student recruitment attractiveness and the management of bullying at public junior high schools (SMP Negeri) in North Prabumulih District. The research focus includes the role of leadership in branding, factors influencing prospective students' interest, and anti-bullying policies implemented by the principal.A qualitative approach with a descriptive case study design was employed. The research was conducted at SMP Negeri 1 Prabumulih (an established school) and SMP Negeri 13 Prabumulih (a newly established school). Data were collected through observation, in-depth interviews with key informants (principals, vice-principals, guidance counselors, supervisors, and media representatives), and documentation. Qualitative data an alysis was used to identify patterns, similarities, and differences in strategies between the two schools. The results indicate that: (1) The principal's strategy for enhancing school image in the established school focuses on maintaining quality consistency and a long-standing reputation, while the new school emphasizes identity formation, brand awareness, and building public trust through the publication of positive activities. (2) The attractiveness of student recruitment is influenced by academic reputation, facilities, discipline, and a conducive learning environment. The new school specifically highlights character building and religious programs, such as Quranic literacy (Baca Tulis Al-Qur'an), to attract public interest. (3) Bullying management is conducted through preventive and curative approaches, involving synergy between the principal, guidance counselors, homeroom teachers, and parents through anti-bullying socialization, character development, and problem-solving mediation. In conclusion, visionary, communicative, and collaborative school leadership is the primary key to building a positive school image. Synergy between all school members and external stakeholders is essential to create an educational environment that is safe, character-driven, and highly competitive.